From Concept to Crystals via Prediction: Multi‐Component Organic Cage Pots by Social Self‐Sorting. Issue 45 (24th September 2019) - Greenaway, Rebecca L.; Santolini, Valentina; Pulido, Angeles; Little, Marc A.; Alston, Ben M.; Briggs, Michael E.; Day, Graeme M.; Cooper, Andrew I.; Jelfs, Kim E.
Abstract: We describe the a priori computational prediction and realization of multi‐component cage pots, starting with molecular predictions based on candidate precursors through to crystal structure prediction and synthesis using robotic screening. The molecules were formed by the social self‐sorting of a tri‐topic aldehyde with both a tri‐topic amine and di‐topic amine, without using orthogonal reactivity or precursors of the same topicity. Crystal structure prediction suggested a rich polymorphic landscape, where there was an overall preference for chiral recognition to form heterochiral rather than homochiral packings, with heterochiral pairs being more likely to pack window‐to‐window to form two‐component capsules. These crystal packing preferences were then observed in experimental crystal structures. Abstract : From molecular structure to solid‐state assembly, a multi‐component self‐sorted organic cage pot is computationally predicted and then synthetically realized. The molecules were formed by the social self‐sorting of a tri‐topic aldehyde with both a tri‐topic amine and di‐topic amine, without using orthogonal reactivity or precursors of the same topicity.